2015
DOI: 10.7314/apjcp.2015.16.16.7343
|View full text |Cite
|
Sign up to set email alerts
|

Importance of FISH combined with Morphology, Immunophenotype and Cytogenetic Analysis of Childhood/Adult Acute Lymphoblastic Leukemia in Omani Patients

Abstract: Genetic changes associated with acute lymphoblastic leukemia (ALL) provide very important diagnostic and prognostic information with a direct impact on patient management. Detection of chromosome abnormalities by conventional cytogenetics combined with fluorescence in situ hybridization (FISH) play a very significant role in assessing risk stratification. Identification of specific chromosome abnormalities has led to the recognition of genetic subgroups based on reciprocal translocations, deletions and modal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
(45 reference statements)
1
7
1
Order By: Relevance
“…This result is comparable to the findings in the earlier studies (Safaei et al, 2013). The incidence of normal karyotype in the previous studies is reported as 48.32% (Siddaiahgari et al, 2015) and 38.30% (Safaei et al, 2013) while it was 31.42% in our study maybe, due to the improvement in the culture techniques and introduction of interphase FISH technique, which led to higher detection of chromosomal abnormalities as in many other studies which used FISH (Goud et al, 2015).…”
Section: Discussion:-contrasting
confidence: 41%
See 3 more Smart Citations
“…This result is comparable to the findings in the earlier studies (Safaei et al, 2013). The incidence of normal karyotype in the previous studies is reported as 48.32% (Siddaiahgari et al, 2015) and 38.30% (Safaei et al, 2013) while it was 31.42% in our study maybe, due to the improvement in the culture techniques and introduction of interphase FISH technique, which led to higher detection of chromosomal abnormalities as in many other studies which used FISH (Goud et al, 2015).…”
Section: Discussion:-contrasting
confidence: 41%
“…The detection can be done by conventional cytogenetic method like karyotyping and molecular cytogenetic techniques like Fluorescent in-situ hybridization (FISH). These methods are helpful in assessing the classification, risk stratification and prediction of outcome of ALL patients (Goud et al, 2015).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
See 2 more Smart Citations
“…Excluded are patients with EBF1/PDGFRB fusion that arose from interstitial deletion of 5q33, occurring within the Philadelphia-like ALL subtype. Del(5q) as a sole clonal cytogenetic abnormality was found in 11 patients (3 with B-ALL, 4 with T-ALL and 4 with unspecified ALL) (Kowalczyk et al, 1985;Brusamolino et al, 1988;Raimondi et al, 1988;Loncarevic et al, 1999;Midmer et al, 1999;Gmidene et al, 2008;Palau et al, 1991;Valtat et al, 1991;Theodossiou et al, 1992;Goud et al, 2015).…”
Section: Cytogenetics Morphologicalmentioning
confidence: 99%